Die moontlikheid van Christelike onderwys in Suid-Afrika ná 1994 - Walt, J. L. van der (Koers, 1997)
The possibility of Christian education in South Africa after 1994Conditions in South Africa have become decidedly unfavourable for the continued practice of Christian education in schools. A culture of fundamental human rights has become firmly established, which, among others, has resulted in the arrival of a secular-humanist educational dispensation. The issue facing the Christian community is how to exploit the prevailing conditions for the survival of Christian education in the system. The research reported in this article has revealed that the new system hinges on four principles, and that an understanding of these principles can afford scope and latitude for Christian education. The four principles are analysed in some detail with reference to a Constitutional Court decision and recent legislation.